Thoracoscopic treatment of benign esophageal tumors - Neoral, Čestmír (Termedia Publishing House, 2012)
INTRODUCTION: Gastrointestinal stromal tumors are among the most frequent mesenchymal tumors of the gastrointestinal tract; the incidence of these tumors in the esophagus is less than 5%. Prognosis depends on localization, size, mitotic activity and possible invasion of surrounding structures. Minimally invasive surgery may be maximally utilized for removal of these tumors from the esophageal wall. This operation is usually performed thoracoscopically or laparoscopically and using the “rendez-vous” method – with endoscopic navigation. AIM: To evaluate a set of patients with benign tumor of the esophagus who were operated on at the First Department of Surgery from 2006 to 2011. MATERIAL AND METHODS: In the years 2006-2011 a total of 11 patients with benign tumors of the esophagus underwent operation. RESULTS: Of the 11 patients with esophageal tumor, 5 were diagnosed with gastrointestinal stromal tumor, 5 with leiomyoma and in one patient the lesion was described as heterotopy of the pancreas. We used the minimally invasive rendez-vous method with endoscopic navigation in 9 cases. All patients healed primarily and were released from hospital on the 4(th)-7(th) day. These patients are being followed up as outpatients and recurrence of the tumor has not been observed in any of them. CONCLUSIONS: Minimally invasive treatment of benign tumors of the esophageal wall is considered to the method of choice. Due to possible complications and the need for subsequent therapy in some patients, these procedures should be centralized to departments with experience in esophageal, thoracic and minimally invasive surgery.